Assessment of different herbicides on weed suppression and yield of groundnut (Arachis hypogaea L.): ASSESSMENT OF DIFFERENT HERBICIDES ON WEED SUPPRESSION AND YIELD OF GROUNDNUT - V PRATAP SINGH; V C DHYANI; AKSHITA BANGA; ABNISH KUMAR; NEETA TRIPATHI; NEEMA (Journal of Oilseeds Research, 2014)
Experiment was conducted at Norman E. Borlaug Crop Research Centre, G. B. Pant University of Agriculture and Technology, Pantnagar to evaluate the performance of quizalofop ethyl sponsor sample to its market sample available for weed suppression and its impact on groundnut yield during kharif 2012. The major weed flora in the experimental plots were Echinochloa colona (39.2%), Eleusine indica (28.0%), Parthenium hysterophorus (7.5%) and Mollugo stricta (3.7%) and Digera arvensis (3.7%). It was found that among the herbicides, post-emergence application of quizalofop ethyl sponsor sample at 50 g a.i./ha was found to be most effective weed management practice in reducing the density and dry weight of weeds with higher weed control efficiency, higher yield (981 kg/ha) and yield attributes being at par with its market sample applied at 50 g a.i./ha. The reduction in kernel yield in unweeded check was 77.6% compared to best weed management practices (quizalofop ethyl sponsor sample @ 50 g a.i./ha). Post emergence application of imazethapyr @ 150 g a.i./ha was found more effective in suppressing broad leaf weeds in groundnut.